Kajian Enso, Hubungannya Dengan Suhu Permukaan Laut Di Teluk Bone - Kusriyati (CV. PUSDIKRA MITRA JAYA, 2022)
ENSO (El Nino Southern Oscillation) that occurs in the eastern tropical Pacific Ocean has an impact on Indonesian seas. Bone Bay which constitutes a part of Indonesian seas in eastern Indonesia is also estimatedly influenced by ENSO. The purposes of this study are to: 1) determine the characteristics of sea surface temperature (SST) in Bone Bay; and 2) determine the relationship between ENSO and SPL. The Southern Oscillation Index (SOI) data during 2003-2012 period have downloaded from the website of the Australian Bureau of Meteorology (BoM), while the SPL data in Bone Bay from MODIS satellite imagery measurement have downloaded from NASA’s website. The set net catch data were obtained from the set net data of each hauling from 2008 to 2011. Descriptive and quantitative analysis is employed to answer the first purpose. Correlation analysis was used to answer the second purposes. SST in Bone Bay is relatively high during West Monsoon with a temperature range of 29.8 to 32oC and relatively low during East Monsoon with a range of 28.1 to 30.5 oC. There seems to be a weak positive relationship between SOI and SPL. It happens because the semi-confined ecosystem of Bone Bay gets more water-mass influences from the surrounding area than that ENSO in Pasifik Ocean.